The fleas (Insecta: Siphonaptera) parasites of Sigmodontine rodents (Cricetidae) from Northern Patagonia, Argentina - Sánchez, Juliana Patricia (2013)
The flea fauna of Patagonia in Argentina comprises about 50% of the total species and subspecies known for Argentina. Given the high diversity of environments and the rich assemblage of sigmodontine rodents of the Patagonian region, flea richness is probably underestimated. In the present study, 16 species and subspecies of fleas parasitizing sigmodontines from Northern Patagonia are reported. Fifteen new parasite–host associations and new records of geographical distribution are reported. The results suggest the coexistence of an endemic flea fauna (Tetrapsyllus (Tetrapsyllus) tantillus; Tetrapsyllus (Tetrapsyllus) rhombus; Ectinorus (Ectinorus) spiculatus; Agastopsylla boxi boxi; and Sphinctopsylla ares) with other species and genera that occur mainly at lower latitudes than those of Patagonia (Tetrapsyllus (Phylliver) bleptus; Ectinorus (Ectinorus) hapalus and Polygenis (Polygenis) rimatus). Considering that the same situation occurs with some species and genera of their sigmodontine hosts, future studies will allow us to determine the distributional limits of each flea taxon and analyze the influence of host geographical distribution.